PEMBAHARUAN PERATURAN DAERAH PASCA BERLAKU UNDANG-UNDANG DESA TAHUN 2014 DALAM MENJAGA EKSISTENSI NEGERI DI KABUPATEN MALUKU TENGAH: Indonesia - Pattinasarany, Yohanes; Lainsamputty, Natanel; Pattipawae, Dezonda Rosiana (Penerbit Universitas Atma Jaya Yogyakarta, 2024)
Law No. 6 of 2014 stipulates 2 (two) types of villages, namely villages and customary villages. Negeri is one form of customary village in Central Maluku Regency. Law No. 6 of 2014 requires the district/city government including the Central Maluku Regency government to determine customary villages. The determination of customary villages is carried out after the arrangement of customary law community units has been carried out. However, for almost 9 (nine) years since the enactment of Law No. 6 of 2014, the Central Maluku Regency Government has not taken any legal legitimizing action regarding the existence of negeri as a form of customary village. For this reason, the problem that will be studied in this writing is what are the legal implications for the existence of negeri after the enactment of Law No. 6 of 2014. The type of research chosen in studying the substance of this research is normative legal research, with the approach of Law No. 6 of 2014 and implementing regulations as the basis for the study in answering the renewal of Regional Regulations in maintaining the existence of Negeri in Central Maluku Regency. This study shows that the legal implications for the existence of the country after the enactment of Law No. 6 of 2014 are that the Central Maluku Regency Government must legitimize the existence of the country as a form of traditional village through the arrangement of customary law community units and designated as a country. The arrangement of customary law community units is carried out by the customary law community unit arrangement committee formed by the Regent. The identification results are determined by the Regent's decision as the basis for the formation of regional regulations on the determination of the country. In reality, the determination of customary law community units have not been carried out by the local government. This condition causes the existence of the country to have no legal legitimacy. In addition, the Central Maluku Regency Government must also update various regional regulations as the legal basis for the implementation of the country government in Central Maluku Regency.